1997
DOI: 10.1002/(sici)1097-0142(19970301)79:5<1037::aid-cncr22>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I and pharmacokinetic study of high dose tamoxifen and weekly cisplatin in patients with metastatic melanoma

Abstract: or regression was documented, the patients received a second 3-week cycle of 2 Department of Medicine, University of Califor-DDP and were then reevaluated for response. Patients with progressive disease nia-San Diego, La Jolla, California.were removed from the study. 3 Department of Pharmaceutical Sciences, Med- RESULTS.In 25 consecutive patients, the overall response rate was 20%. No reical University of South Carolina, Charleston, sponses were observed in patients treated with TAM at a dose of õ240 mg/day. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Additionally, another work has indicated that more than 70% of NSCLC tumors showed reduced p27 KIP1 immunoreactivity and the expression of this CDKI was found to be a favorable prognostic factor for patient survival (Yatabe et al, 1998). It should be noted that the concentration of Tam used in this study can be attained in serum with high-dose Tam therapy (Trump et al, 1992;McClay et al, 1997). Collectively, these ®ndings indicate that Tam is a potent inducer of CDKI expression and an eective inhibitor of cell growth in NSCLC cells in vitro and this drug warrants further in vivo study.…”
Section: Kip1mentioning
confidence: 68%
“…Additionally, another work has indicated that more than 70% of NSCLC tumors showed reduced p27 KIP1 immunoreactivity and the expression of this CDKI was found to be a favorable prognostic factor for patient survival (Yatabe et al, 1998). It should be noted that the concentration of Tam used in this study can be attained in serum with high-dose Tam therapy (Trump et al, 1992;McClay et al, 1997). Collectively, these ®ndings indicate that Tam is a potent inducer of CDKI expression and an eective inhibitor of cell growth in NSCLC cells in vitro and this drug warrants further in vivo study.…”
Section: Kip1mentioning
confidence: 68%
“…The use of tamoxifen in this context was based upon previous reported studies from our institution describing synergism between high doses of tamoxifen and platinum chemotherapy. [17][18][19] Prophylactic heparin (5000 units s.c. three times daily day −5 to 0 ) was used to minimize the risk of thromboembolic complications. PBSC +/− BM were re-infused on day 0 as for HDC cycle I.…”
Section: High-dose Chemotherapymentioning
confidence: 99%
“…Furthermore, during the past two decades, over 25 clinical trials have been published reporting the effects of “high dose” tamoxifen (i.e. doses above those needed to inhibit ER activity) ranging from 80 to 720 mg/day (5) to treat non-breast cancers including glioma (6), melanoma (7) and others (8,9), as a single agent or in combination with chemotherapeutics. While of these Phase I and II trials showed variable clinical benefit, they clearly demonstrated the safety of high dose tamoxifen in diverse patient populations.…”
Section: Introductionmentioning
confidence: 99%